(untitled) (Fiep Bulletin - online, 2013)
The studies related to hyperactivity are known since the mid-twentieth century, but with deepening made only in recent decades. This study addresses the influence of school / teacher in the life of a student, since the problem discussed behind deviations the child is emotionally or their social adaptation, damaging then in their school and also affecting their interpersonal contacts. Thus, by means of the analysis, the practice of physical activities behind an improvement in the performance of the child hyperactive. Thus serving as mediator for the treatment of this problem, so that this student is inserted and actively participating in objective manner in class, thus encouraging it to be a critical individual and participatory. For this, it was found that the work between teacher and student must be continuous and that through the experiences the teacher to collaborate with the development of motor and social skills of children. By means of surveys, studies show the possibility of changing these individuals after started the process of working with the practice of physical activities. So the reference point for this work is to examine the theories already developed and discuss to what extent, this can work for the progress of children with hyperactivity, while respecting their particularities and their boundaries, in view of the inclusion of that person not only the environment school, but also in society where it is inserted.